PELATIHAN, PENDAMPINGAN MANAJEMEN, DAN DIGITALISASI DESA WISATA BRUMBUN KABUPATEN MADIUN MELALUI PENERAPAN APLIKASI E-COMMERCE - Iqbal Ramadhani Mukhlis (Jurnal Pengabdian kepada Masyarakat, 2026)
Traditional promotion (word of mouth) and booking management (via WhatsApp) are major challenges for MSMEs and Pokdarwis in Brumbun Tourism Village. This community service activity aims to bridge this digital problem by designing and implementing appropriate technological solutions. The method used was the participatory development of the WooCommerce-based e-commerce application "brumbun.deswita," designed to be simple and intuitive to meet partner needs. The development of this platform was accompanied by digital literacy training and intensive mentoring to improve human resource capacity. The program's success was measured using pre-test and post-test questionnaires to evaluate the training's effectiveness. The evaluation results showed a significant increase in participant understanding of 50.2%, with the highest increase in operational technical skills, specifically "Booking Confirmation and Management" (score increased from 0.65 to 1.00). The application received a positive response from participants and successfully transformed business processes from manual recording to a centralized digital dashboard. This activity successfully laid the foundation for digitalization, shifting partners' mindsets towards more professional business management in Brumbun Tourism Village.